Perancangan Design Order Management System Berbasis Web dengan Metode Design Thinking - Sinaga, Louis Godson; Johan, Meliana Christianti (Maranatha University Press, 2024)
Company in Bandung conducts online sales in various marketplace to reach all customer. Transactions that have been made by customer will enter each marketplace used by the company, but the sales admin must open each marketplace to find out the transactions that have been made and also have to open one marketplace to add product and add voucher and others. This is less effective and makes it difficult for sales admin from company in Bandung if there are many transactions from customer and many product additions in each marketplace. Therefore, Order Management System (OMS) is very functional for company in Bandung to the facilitate the work of sales admin. Order Management System will be made based on the needs of the sales admin or user by using web-based design thinking method, so that the sales admin can access through the website. The research conducted only focuses on designing a web-based design of the order management system, so that the results of the study will discuss the design of the order management system which contains features based on the needs of the sales admin or user.